Association between transcription factors expression and growth patterns of nonfunctioning pituitary adenomas - Jiakun Xu; Shaolin Zhang; Weijie Su; Jia Yang; Lixuan Yang; Xixi Li (Scientific Reports)
Abstract Transcription factors (TFs), including steroidogenic factor-1 (SF-1), T-box transcription factor (TPIT) and pituitary transcription factor–1 (PIT-1), play a pivotal role in the cytodifferentiation of adenohypophysis. However, the impact of TFs on the growth patterns of nonfunctioning pituitary adenomas (NFPAs) remains unclear. This study aims to investigate the correlation between the expression of TFs and NFPAs growth patterns. Preoperative MRI in 171 patients who underwent surgery for nonfunctioning pituitary macroadenomas were analyzed to determine tumor growth patterns. Immunohistochemical staining for transcription factors PIT-1, TPIT, and SF-1 was done on all samples. Extrasellar growth was divided into three principal directions: infrasellar, suprasellar and lateral cavernous sinus invasion (CSI). Suprasellar extension was defined as tumor extension superior to the tuberculum sellae-dorsum sellae line, inferior extension as invasion through the sellar floor into the sphenoid sinus or clivus and CSI as Knosp grading score of 3 ~ 4. Statistical analysis to compare the groups was conducted using the Fisher’s exact test and t-test. TPIT-expressing tumors were more likely to exhibit combined infrasellar extension (55.17 vs 17.70%, p < 0.0001), as well as isolated infrasellar extension (18.97 vs 0%, p < 0.0001) compared to SF-1-expressing tumors. Conversely, SF-1-expressing tumors were more likely to exhibit combined suprasellar extension (92.92 vs 77.59%, p = 0.0061), as well as isolated suprasellar extension (75.22 vs 41.38%, p < 0.0001). TPIT-expressing tumors had a significantly higher CSI invasion (55.17 vs 35.40%, p = 0.0148). The mean maximal tumor diameter in TPIT and SF-1 macroadenomas was similar (28 vs 26 mm, p = 0.1213). The expression of TFs affects the extrasellar growth pattern of NFPAs. TPIT tumors exhibit a higher propensity for bone invasion and CSI, while SF-1 tumors tend to extend into the suprasellar region. Isolated infrasellar extension is specific to TPIT tumors and can serve as a radiologic sign to distinguish between TPIT tumors and SF-1 tumors.